2014
DOI: 10.1038/nclimate2301
|View full text |Cite
|
Sign up to set email alerts
|

Recently identified microbial guild mediates soil N2O sink capacity

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
312
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 402 publications
(346 citation statements)
references
References 30 publications
29
312
3
2
Order By: Relevance
“…However, dissociation curve analysis following quantitative real-time PCR (qPCR) showed that there was sometimes minor unspecific coamplification, suggesting that the abundance of nosZ II organisms may be overestimated in some cases. The nosZ N 2 O reducers are critical in determining the soil N 2 O sink capacity (47), and conceivably the abundance of nosZ genes and/or mRNA should be correlated negatively with N 2 O emissions (48). However, no such correlation was found in the present study, suggesting that the correlation between nosZ genes and N 2 O emissions is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…However, dissociation curve analysis following quantitative real-time PCR (qPCR) showed that there was sometimes minor unspecific coamplification, suggesting that the abundance of nosZ II organisms may be overestimated in some cases. The nosZ N 2 O reducers are critical in determining the soil N 2 O sink capacity (47), and conceivably the abundance of nosZ genes and/or mRNA should be correlated negatively with N 2 O emissions (48). However, no such correlation was found in the present study, suggesting that the correlation between nosZ genes and N 2 O emissions is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that soil N 2 O emissions are predominantly determined by nirK-, rather than by nirS-type microorganisms. Thus, the nirS/nirK ratio may be negatively correlated with the soil N 2 O sink capacity [58,59]. Therefore, the increased nirK gene abundance in combination with the consistent or decreased amounts of nirS and nosZ genes can be seen as a predictor of enhanced potential for N 2 O emissions from infested forest sites.…”
Section: The Varying Effects On Denitrification Genesmentioning
confidence: 99%
“…Proxies for the capacity of soils to store/lose C and to enhance/reduce GHGs emissions can help to make choices on land use and soil management Soil C saturation capacity (Angers et al, 2011;Wiesmeier et al, 2014) has been proposed to estimate the potential gain of soil organic C. Its relevance for predicting soil C storage remains to be evaluated (O'Rourke et al, 2015;Dignac et al, 2017) Physical fractionation of soil organic C (particulate organic matter fraction) and thermal analysis have been proposed to estimate the potential for soil C loss (Dignac et al, 2017 and references therein) Soil capacity to reduce N 2 O (Hénault et al, 2001;Jones et al, 2014) Guidelines to estimate GHGs emissions from soil using models…”
Section: Resultsmentioning
confidence: 99%